2001
DOI: 10.1191/0748233701th101oa
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos content of omentum and mesentery in nonoccupationally exposed individuals

Abstract: Asbestos fibers in occupationally exposed individuals relocate from the lung to extrapulmonary sites. A mechanism for relocation is via the lymphatic circulation. Indeed, asbestos fibers have been found in lymph nodes as well as pleural plaques. Our laboratory has recently shown that asbestos fibers also reach the mesentery and omentum in the peritoneal area where a small percentage of mesotheliomas occurs in exposed individuals. The present study uses light and analytical transmission electron microscopy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…These values are three orders of magnitude higher than previously reported asbestos concentrations in the omentum and mesentery of patients with mesothelioma (range 0.0002-0.0066 million f/g fibers >1 mm in length) [Dodson et al, 2000[Dodson et al, , 2001. The lung asbestos concentrations in these patients were similar to those found in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These values are three orders of magnitude higher than previously reported asbestos concentrations in the omentum and mesentery of patients with mesothelioma (range 0.0002-0.0066 million f/g fibers >1 mm in length) [Dodson et al, 2000[Dodson et al, , 2001. The lung asbestos concentrations in these patients were similar to those found in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Dodson et al [2000Dodson et al [ , 2001 have detected asbestos fibers in the omentum and mesentery of patients with mesothelioma and also in nonoccupationally exposed persons. The route of penetration of asbestos fibers to the peritoneal space is still uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that it is not just the size and shape of the various asbestos fibers that are important in its ability to produce disease but other factors may play a role in the carcinogenicity of the mineral fiber [Wagner, 1980;Wylie et al, 1987]. Studies have also found that the majority of asbestos fibers in lung and mesothelial tissues were shorter than 5 mm in length, thus indicating the ability of the shorter fibers to reach the tumor site, remain there, and, therefore, their role in the etiology of disease is implicated [Dodson et al, 2001;Suzuki and Yuen, 2002]. National Institute for Occupational Safety and Health (NIOSH) research has found that in typical occupational environments fibers shorter than 5 mm in length outnumber the longer fibers by a factor of 10 or more [Dement and Wallingford, 1990].…”
Section: Toxicity Of Short Asbestos Fibersmentioning
confidence: 97%
“…The authors also reported that the likelihood of translocation was strongly related to the thinness of the fiber [72]. Asbestos fibers have been found in mesenteric lymph nodes in autopsies of individuals with asbestos exposure [73], supporting the hypothesis that lymph drainage is an important translocation mechanism for asbestos in the human body [73,74)]. Kurimoto et al [75] reported this in a case of peritoneal mesothelioma asbestos fibers at concentrations >10,000 fibers/g dry tissue, which were found in all samples of intra-abdominal tissue examined (except in the small intestine.…”
Section: Experimental Datamentioning
confidence: 83%
“…There are multiple studies in which women were exposed to amphibole and/or chrysotile asbestos and developed peritoneal mesothelioma [41,43,[51][52][53]57,58,73,[79][80][81][82][83][84][85][86][87] There are additional studies of female peritoneal mesothelioma. Keal [88] reported eight female cases of peritoneal cancers on an examination of records from London hospital records and specimens (four of which were probably from the ovary and four from the peritoneum) who all had asbestosis.…”
Section: Are Peritoneal Mesotheliomas In Women Attributable To Asbestos?mentioning
confidence: 99%